Preparing for a Safety Evaluation of Rotavirus Vaccine Using Health Services Data in Ontario: The Development of a Diagnostic Algorithm for Intussusception, an Estimation of Baseline Incidence and an Evaluation of Methods - Ducharme, Robin Beverly (Université d'Ottawa / University of Ottawa, 2014)
In view of the recent implementation of a publicly funded rotavirus vaccination program in Ontario, we undertook studies to help guide the design of a safety evaluation of the vaccine with respect to intussusception. We used administrative data to develop and validate an algorithm for intussusception, and quantified its incidence in Ontario. We also conducted a systematic review of study designs used to evaluate post-licensure vaccine safety, and discussed each design’s strengths and weaknesses. The validated algorithm for intussusception was sensitive (89.3%) and highly specific (>99.9%). We observed the highest mean incidence (34 / 100,000) in males <1 year of age. While other designs are more robust, the inability to ascertain individual vaccination status from Ontario’s administrative data dictated our selection of an ecological design for safety evaluation of rotavirus vaccine. Data assimilated from this thesis represent a critical step toward the timely evaluation of rotavirus vaccine safety in Ontario.
Keywords: Rotavirus vaccine; Intussusception; Algorithm; Health Services Data; Methodological Review